AN ANALYSIS OF MOVE AND LINGUISTIC CHARACTERISTICS OF HOTEL HOMEPAGES - Sitthanakul, Kawita; Dhanesschaiyakupta, Ubon (PEOPLE: International Journal of Social Sciences, 2017)
This study’s aim is to analyze the move structure and linguistic characteristics of hotel homepages for the three hotel classesthe similarities and differences among the three classes. Data was collected from 138 hotel homepages in Pattaya, Thailand. The framework of Askehave and Nielsen (2005) and Leech’s (1966) were adopted in this study. The results revealed that a total of five moves were found across all homepages; nevertheless, there were some differences in a frequency of occurrence and also the level of linguistic descriptions among the three classes. Moreover, each move and step indicated its remarkable linguistics characteristic.The findings in the study would be beneficial to learners, instructors, practitioners in English for Specific Purposes (ESP) in general and hotel Web site designers in particular. The further study should investigate the move structure in all hotel star ratings in order to provide a typical structure of move analysis. Furthermore, the images appearing on the homepages should be included in the analysis to fulfill the communicative purpose for online hospitality.